Confidence in self-care after heart failure hospitalization. Issue 1 (January 2023) - Hashimoto, Shun; Kitakata, Hiroki; Kohsaka, Shun; Fujisawa, Daisuke; Shiraishi, Yasuyuki; Nakano, Naomi; Sekine, Otoya; Kishino, Yoshikazu; Katsumata, Yoshinori; Yuasa, Shinsuke; Fukuda, Keiichi; Kohno, Takashi
Abstract: Background: Understanding patient perspectives of self-care is critical for improving multidisciplinary education programs and adherence to such programs. However, perspectives of self-care for patients with heart failure (HF) as well as the association between patient perspectives and patient-physician communication remain unclear. Methods: Confidence levels regarding self-care behaviors (eight lifestyle behaviors and four consulting behaviors) and self-monitoring were assessed using a self-administered questionnaire survey, which was directly distributed by dedicated physicians and nurses to consecutive patients hospitalized with HF in a tertiary-level hospital. Patient-physician communication was evaluated according to the quality of physician-provided information regarding "treatment and treatment choices" and "prognosis" using the Prognosis and Treatment Perception Questionnaire. Out of 202 patients, 187 (92.6 %) agreed to participate, and 176 completed the survey [valid response rate, 87.1 %; male, 67.0 %; median age, 73 (63–81) years]. Multivariate logistic regression analyses were conducted to predict low confidence in self-care (score in the lowest quartile). Results: High confidence (confident or completely confident >75 % of patients) was observed for all self-care behavior categories except low-salt diet (63.1 %), regular exercise (63.1 %), and flu vaccination (65.9 %). Lower confidence in self-care behavior was associated with low quality of patient-physician communication. With regard to self-monitoring, 62.5 % of patients were not confident in distinguishing worsening symptoms of HF from other diseases; non-confidence was also associated with low quality of patient-physician communication. Conclusions: Hospitalized patients with HF had low confidence regarding regular exercise, salt restriction, and flu vaccination. The results also suggest patient-physician communication affects patient confidence. Graphical abstract: Regular exercise (36.9 %), low-salt diet (36.9 %), and flu vaccination (34.1 %) were the top-ranked self-care behaviors associated with low confidence. Lower confidence levels regarding self-care behavior were associated with low quality of patient-physician communication. In terms of symptom monitoring, approximately 60 % of patients were not confident in distinguishing worsening symptoms of HF from other diseases, which was also associated with low quality of patient-physician communication. HF, heart failure. Unlabelled Image Highlights: Heart failure (HF) patients had low confidence about exercise, salt restriction, and flu vaccination. Patients lacked confidence in the distinction between HF and other disease symptoms. Patient-physician communication was associated with confidence levels in self-care. Medical providers should focus more on improving patient-physician communication.